The Cardiovascular and Cerebrovascular Health in North China From 2006 to 2011: Results From the KaiLuan Study - Yu, Yao; Dong, Zhiyi; Li, Yongjie; Zhang, Jun; Yin, Sufeng; Gao, Xuguang; Wu, Shouling, KaiLuan Study Investigators (Frontiers in Cardiovascular Medicine, 2021)
Background: The American Heart Association (AHA) defined cardiovascular health in terms of four behaviors (smoking, diet, physical activity, body weight) and three factors (plasma glucose, cholesterol, blood pressure) . By this definition, the prevalence of ideal cardiovascular health behaviors and factors is negatively correlated with all-cause mortality and risks of cardiovascular and cerebrovascular disease and malignancy. According to the concept of definition, we put forward the concept of cardiovascular and cerebrovascular health and analyzed trends in cardiovascular and cerebrovascular health behaviors and factors in the population of the KaiLuan study for 2006–2011 reported the results and provided evidence for prevention. Methods and Results: We calculated the prevalence of cardiovascular and cerebrovascular health behaviors and factors from KaiLuan data for 2006–2007, 2008–2009 and 2010–2011. The prevalence of ideal cardiovascular and cerebrovascular health behaviors and factors is low in the KaiLuan population. Conclusions: The prevalence of ideal cardiovascular and cerebrovascular health behaviors and factors is low in the KaiLuan population. Clinical Trial Registration: http://www.chictr.org/cn/proj/show.aspx?proj=1441; unique identifier: ChiCTR-TNC-11001489.